Changes in Astroglial Markers in a Maternal Immune Activation Model of Schizophrenia in Wistar Rats are Dependent on Sex - de Souza, Daniela F.; Wartchow, Krista M.; Lunardi, Paula S.; Brolese, Giovana; Tortorelli, Lucas S.; Batassini, Cristiane; Biasibetti, Regina; Gonçalves, Carlos-Alberto (Frontiers in Cellular Neuroscience, 2015)
Data from epidemiological studies suggest that prenatal exposure to bacterial and viral infection is an important environmental risk factor for schizophrenia. The maternal immune activation (MIA) animal model is used to study how an insult directed at the maternal host can have adverse effects on the fetus, leading to behavioral and neurochemical changes later in life. We evaluated whether the administration of LPS to rat dams during late pregnancy affects astroglial markers (S100B and GFAP) of the offspring in later life. The frontal cortex and hippocampus were compared in male and female offspring on postnatal days (PND) 30 and 60. The S100B protein exhibited an age-dependent pattern of expression, being increased in the frontal cortex and hippocampus of the MIA group at PND 60, while at PND 30, male rats presented increased S100B levels only in the frontal cortex. Considering that S100B secretion is reduced by elevation of glutamate levels, we may hypothesize that this early increment in frontal cortex tissue of males is associated with elevated extracellular levels of glutamate and glutamatergic hypofunction, an alteration commonly associated with SCZ pathology. Moreover, we also found augmented GFAP in the frontal cortex of the LPS group at PND 30, but not in the hippocampus. Taken together data indicate that astroglial changes induced by MIA are dependent on sex and brain region and that these changes could reflect astroglial dysfunction. Such alterations may contribute to our understanding of the abnormal neuronal connectivity and developmental aspects of SCZ and other psychiatric disorders.